2013
DOI: 10.1063/1.4810016
|View full text |Cite
|
Sign up to set email alerts
|

CO2 sensing at room temperature using carbon nanotubes coated core fiber Bragg grating

Abstract: The sensing of carbon dioxide (CO2) at room temperature, which has potential applications in environmental monitoring, healthcare, mining, biotechnology, food industry, etc., is a challenge for the scientific community due to the relative inertness of CO2. Here, we propose a novel gas sensor based on clad-etched Fiber Bragg Grating (FBG) with polyallylamine-amino-carbon nanotube coated on the surface of the core for detecting the concentrations of CO2 gas at room temperature, in ppm levels over a wide range (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…The functional material also imparts selectivity to the sensor if it reacts only to the target analyte. One of the key contributions of this work is to demonstrate that the polymer Polyhexamethylene Biguanide (PHMB) functions effectively as a refractometric sensing layer for CO 2 gas without requiring the addition of water vapor, as is the case for previously reported functional materials [8,9]. PHMB belongs to a class of guanidine derivatives which have been known to function in both solution and solid states to reversibly bind with CO 2 gas molecules.…”
Section: Microring Refractometric Co 2 Gas Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The functional material also imparts selectivity to the sensor if it reacts only to the target analyte. One of the key contributions of this work is to demonstrate that the polymer Polyhexamethylene Biguanide (PHMB) functions effectively as a refractometric sensing layer for CO 2 gas without requiring the addition of water vapor, as is the case for previously reported functional materials [8,9]. PHMB belongs to a class of guanidine derivatives which have been known to function in both solution and solid states to reversibly bind with CO 2 gas molecules.…”
Section: Microring Refractometric Co 2 Gas Sensormentioning
confidence: 99%
“…However, while several refractometric CO 2 sensors using different functionalization materials have been reported, they typically require a humidified gas environment to operate. For example, a fiber Bragg grating sensor was reported in [8] which employs polyallylamine-amino-carbon nanotubes for detecting CO 2 at fairly large concentrations, in the 1000 -4000 ppm range, under a constant relative humidity of 47%. A surface plasmon resonance sensor functionalized with a polymer blend was also reported in [9] for detecting dissolved and humidified gaseous CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The maximum photosensitivity of graphene‐FBG device was found to be 95 pm mW −1 with the limit of detection (LoD) of 210 µW (LoD = resolution of the OSA (20 pm)/sensitivity (95 pm mW −1 )). The LoD can be further reduced to nW by using high resolution interrogator system, using micro or etched FBG devices and by increasing the absorption of graphene by constructing heterostructures with other 2D materials.…”
Section: Resultsmentioning
confidence: 99%
“…One recent method to increase the mechanical properties of adhesives is through the addition of carbonnanotubes (CNTs). Previous authors have demonstrated CNT coatings on optical fibers, to create nonlinear optical interactions, however not at sufficient densities to significantly change their mechanical properties [10][11][12][13][14][15][16]. Typically, adding CNTs to bulk polymers or coatings results in a maximum performance gain at around a few percent weight addition [17,18].…”
Section: Introductionmentioning
confidence: 99%